3PC-017 Increasing pharmacy productivity by expanding the role of the intravenous compounding robot in a comprehensive cancer centre. (24th March 2020) - Capilli, M; Federici, M; Comandone, T; Maffeis, G; Foglio, F; Omini, L; Enrico, F
Abstract : Background and importance: In a comprehensive cancer centre, injectable anticancer drugs are compounded in the pharmacy based preparation unit with the compounding robot APOTECAchemo to guarantee a high level of quality and safety. In 2018, the oncology pharmacy implemented workflow improvements to manage the growing workload due to the centralisation of the activities of a hospital's satellite pharmacy. Aim and objectives: The aim of the study was to analyse the pharmacy workflow and impact of the robotic system on turnaround time to meet increasing pharmacy productivity. Material and methods: Data were collected from the hospital information system and the workflow management software APOTECAmanager, and examined over a 2 year period (2017–2018). The total annual throughput in terms of doses prepared and patients treated were determined. Productivity, number of active ingredients processed, average usage time per day and dosage accuracy (ie, per cent discrepancy between compounded and prescribed dose) were calculated for the robotic system. Medication turnaround time (MTAT) for outpatients, defined as total time from the release of a medication order by the prescriber to administration of the medication to the patient, was measured over 3 months. Results: Overall, the annual doses prepared and patients treated increased by 18% (from 18 574 doses/year in 2017 to 22 754 doses/year in 2018) and by 10% (from 1421 patients/year in 2017 to 16 604 patients/year in 2018), respectively. The robot was used to compound 47% of the overall doses prepared in 2017 (8677 doses/year) compared with 57% in 2018 (13 047 doses/year). The average usage time of the robot increased by 58% (from 2.09 hours/day in 2017 to 5.01 hours/day in 2018), while the number of active ingredients processed rose from 20 in 2017 to 30 in 2018. Overall, 95.0% of doses prepared with the robot showedan error <2.0%. The average MTAT for outpatients was lowered by 24.7% (from 2.8 hours in 2017 to 2.1 hours in 2018). Conclusion and relevance: The study revealed that the oncology pharmacy was able to meet escalating demands of ready to administer anticancer drugs by satellite hospitals, by making more use of the robotic system without increasing pharmacy staff. The pharmacy workflow changes enabled reduced MTAT and better order processing efficacy, thereby providing improved patient care. References and/or acknowledgements: No conflict of interest.